Exosomes Derived from Human Primary and Metastatic Colorectal Cancer Cells Contribute to Functional Heterogeneity of Activated Fibroblasts by Reprogramming Their Proteome. Issue 8 (31st January 2019) - Rai, Alin; Greening, David W.; Chen, Maoshan; Xu, Rong; Ji, Hong; Simpson, Richard J.
Abstract: Cancer‐associated fibroblasts (CAFs) are a heterogeneous population of activated fibroblasts that constitute a dominant cellular component of the tumor microenvironment (TME) performing distinct functions. Here, the role of tumor‐derived exosomes (Exos) in activating quiescent fibroblasts into distinct functional subtypes is investigated. Proteomic profiling and functional dissection reveal that early‐ (SW480) and late‐stage (SW620) colorectal cancer (CRC) cell‐derived Exos both activated normal quiescent fibroblasts (α‐SMA −, CAV +, FAP +, VIM + ) into CAF‐like fibroblasts (α‐SMA +, CAV −, FAP +, VIM + ). Fibroblasts activated by early‐stage cancer‐exosomes (SW480‐Exos) are highly pro‐proliferative and pro‐angiogenic and display elevated expression of pro‐angiogenic (IL8, RAB10, NDRG1) and pro‐proliferative (SA1008, FFPS) proteins. In contrast, fibroblasts activated by late‐stage cancer‐exosomes (SW620‐Exos) display a striking ability to invade through extracellular matrix through upregulation of pro‐invasive regulators of membrane protrusion (PDLIM1, MYO1B) and matrix‐remodeling proteins (MMP11, EMMPRIN, ADAM10). Conserved features of Exos‐mediated fibroblast activation include enhanced ECM secretion (COL1A1, Tenascin‐C/X), oncogenic transformation, and metabolic reprogramming (downregulation of CAV‐1, upregulation of glycogen metabolism (GAA), amino acid biosynthesis (SHMT2, IDH2) and membrane transporters of glucose (GLUT1), lactate (MCT4), and amino acids (SLC1A5/3A5)). This study highlights the role of primary and metastatic CRC tumor‐derived Exos in generating phenotypically and functionally distinct subsets of CAFs that may facilitate tumor progression.